Study of haematological parameters in malaria - Surve, Ketaki Motram; Kulkarni, Anjali S.; Rathod, Santosh G.; Bindu, Rajan S. (International Journal of Research in Medical Sciences, 2017)
Background: Malaria causing plasmodia are parasites of blood and hence induce haematological alterations. The haematological changes that have been reported to accompany malaria include anemia, thrombocytopenia and leucocytosis, leukopenia, mild to moderate atypical lymphocytosis, monocytosis, eosinophilia and neutrophilia. Methods: Total hundred smear positive malaria cases were taken and various hematological parameters and biochemical parameters were studied. Results: Out of 100 smear positive cases, P. vivax was positive in 55 cases while P. falciparum was positive in 45 cases. It was seen in 86.67% of falciparum Malaria patients and in 72.72% of vivax Malaria patients. Severe anemia was seen in 9% of patients. Normocytic normochromic blood picture was the most common type in anaemic patients (51.89%). Thrombocytopenia was seen in 71% of the patients. Mild thrombocytopenia was more common and present in 52% of patients while Severe thrombocytopenia was seen in 19% of cases. In falciparum malaria thrombocytopenia was present in 66.66% of the patients while it was present in 74.54% of the patients in vivax malaria. Total Leucocyte Count was normal in 72% of the patients. Conclusions: Various haematological findings can help in early diagnosis of malaria which is essential for timely and appropriate treatment which can limit the morbidity and prevent further complications.